Presence of Enrique Díez-Canedo’s and Fernando Fortún’s La poesía francesa moderna in Los heraldos negros and Trilce - Pagni, Andrea (2020)
This article focuses on the impact of La poesía francesa moderna on the poetry and poetics of César Vallejo. I first examine how Vallejo processes and cites his readings in his thesis El Romanticismo en la poesía castellana and briefly describe the anthology of Díez-Canedo and Fortún. I then situate Vallejo and his reading of French symbolist poetry in translation in the Peruvian socio-literary context between 1914 and 1922, the year Trilce was published. Finally, I analyse the presence of the anthology in the poems «Simbolista», the first version of «Retablo», from Los heraldos negros, and in Trilce «LV».